Climate change mitigation potential of wetlands and the cost-effectiveness of their restoration. Issue 5 (6th October 2020) - Taillardat, Pierre; Thompson, Benjamin S.; Garneau, Michelle; Trottier, Karelle; Friess, Daniel A.
Abstract : The cost-effective mitigation of climate change through nature-based carbon dioxide removal strategies has gained substantial policy attention. Inland and coastal wetlands (specifically boreal, temperate and tropical peatlands; tundra; floodplains; freshwater marshes; saltmarshes; and mangroves) are among the most efficient natural long-term carbon sinks. Yet, they also release methane (CH4 ) that can offset the carbon they sequester. Here, we conducted a meta-analysis on wetland carbon dynamics to (i) determine their impact on climate using different metrics and time horizons, (ii) investigate the cost-effectiveness of wetland restoration for climate change mitigation, and (iii) discuss their suitability for inclusion in climate policy as negative emission technologies. Depending on metrics, a wetland can simultaneously be a net carbon sink (i.e. boreal and temperate peatlands net ecosystem carbon budget = −28.1 ± 19.13 gC m −2 y −1 ) but have a net warming effect on climate at the 100 years time-scale (i.e. boreal and temperate peatland sustained global warming potential = 298.2 ± 100.6 gCO2 eq −1 m −2 y −1 ). This situation creates ambivalence regarding the effect of wetlands on global temperature. Moreover, our review reveals high heterogeneity among the (limited number of) studies that document wetland carbon budgets. We demonstrate that most coastal and inland wetlands have a net cooling effect as of today. This is explained by the limited CH4 emissions that undisturbed coastal wetlands produce, and the long-term carbon sequestration performed by older inland wetlands as opposed to the short lifetime of CH4 in the atmosphere. Analysis of wetland restoration costs relative to the amount of carbon they can sequester revealed that restoration is more cost-effective in coastal wetlands such as mangroves (US$1800 ton C −1 ) compared with inland wetlands (US$4200–49 200 ton C −1 ). We advise that for inland wetlands, priority should be given to conservation rather than restoration; while for coastal wetlands, both conservation and restoration may be effective techniques for climate change mitigation.